Evaluation of Serum Vitamin D Levels in Patients with Carpal Tunnel Syndrome - P Saadat (Babol University of Medical Sciences, 2020)
BACKGROUND AND OBJECTIVE: Low levels of vitamin D are associated with clinical effects such as gastrointestinal disorders, cardiovascular disorders, autoimmune disorders, neuropathic diseases, cancer and metabolic syndrome. Carpal Tunnel Syndrome (CTS) is the most common cause of compression neuropathy, which has recently been linked to vitamin D deficiency in the onset or severity of symptoms. Therefore, this study was performed to evaluate the serum levels of vitamin D in patients with carpal tunnel syndrome. METHODS: This case-control study was performed on 100 patients referred to the neurology clinic of Ayatollah Rouhani Hospital with clinical symptoms of CTS for at least 3 months and 100 patients as a control group who referred to the same clinic for nerve conduction velocity test and did not show symptoms of CTS in clinical examination and electrophysiology. Patients' function, disease severity and pain were measured based on the Boston Carpal Tunnel Questionnaire (BCTQ). Serum vitamin D levels were also measured and compared between the two groups. FINDINGS: The mean age of patients was 43.53±10.68 years and controls were 45.48±7.12 years. The mean serum vitamin D levels in patients and controls were 19.18±11.39 ng/dL and 21.39±15.93 ng/dL, respectively. In controls, 57 women suffered from vitamin D deficiency (p<0.05). There was no significant difference between the two groups in terms of disease severity, function status, pain severity, electrophysiological defect, involved hand, dominant hand and symptoms associated with vitamin D deficiency and there was a negative correlation in vitamin D levels with disease severity, function and pain of patients. CONCLUSION: The results showed that there was a relationship between serum vitamin D levels and gender. In addition, a negative correlation was observed between serum vitamin D levels and patients' disease severity and function and electrophysiological defects.